2020
DOI: 10.1177/1468087420960895
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high-pressure injection variations on the mixing state of underexpanded methane jets

Abstract: This work presents a joint experimental and numerical study of global characteristics and mixing behavior of underexpanded methane jets at high-pressure conditions in a Constant Volume Chamber. Injection pressures of 200, 250, and 300 bar and pressure ratios of 4, 5, 6, 8, and 10 at each of those pressures have been investigated. Tracer LIF with acetone as tracer has been applied to experimentally quantify the mixing of methane and quiescent air. In order to exploit the symmetry of the configuration, accompany… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…At choked flow conditions, the pressure ratio is the most dominant parameter affecting the mass flow [20]. In addition, higher pressure ratios can lead to higher turbulence levels and faster mixing [40] which are particularly influential for direct injection engines. In this study, the effect of pressure ratio on the jet characteristics both by changing P i at a constant P ch and by changing P ch at a constant P i is investigated.…”
Section: Effect Of the Pressure Ratiomentioning
confidence: 99%
“…At choked flow conditions, the pressure ratio is the most dominant parameter affecting the mass flow [20]. In addition, higher pressure ratios can lead to higher turbulence levels and faster mixing [40] which are particularly influential for direct injection engines. In this study, the effect of pressure ratio on the jet characteristics both by changing P i at a constant P ch and by changing P ch at a constant P i is investigated.…”
Section: Effect Of the Pressure Ratiomentioning
confidence: 99%
“…The quantitative interpretation of the processed tracer PLIF images as equivalence ratio fields relies on the procedures outlined in [26,34,35]. The interpretation of measured tracer PLIF intensities as equivalence ratio Φ is governed by the following equation…”
Section: Tracer Plif Image Processing and Transformation To Equivalen...mentioning
confidence: 99%
“…The bulk piston temperature 𝑇𝑇 as well as the air density 𝜌𝜌 air at each time step are calculated from measured piston pressures 𝑝𝑝 in assuming adiabatic compression/expansion. In assuming rotational symmetry of the fuel spray, the proportionality constant 𝐾𝐾 links the injected fuel mass to the volume integrated intensity and is used to transform the quantum yield corrected fluorescence intensity to local fuel density [34,35]. The operation inherently assumes a low tracer concentration so that absorption of laser energy can be neglected and that the excitation energy of the probed transition stays below the saturation limit.…”
Section: Tracer Plif Image Processing and Transformation To Equivalen...mentioning
confidence: 99%
“…The high-pressure NG has its own characteristics. Sakellarakis et al conducted both experimental and numerical simulation research studies of high-pressure methane jets, and the results confirmed the hyperbolic decay of axial fuel concentration and the Gaussian shape of traverse concentration profiles in the self-similar region of the jets. Cheng et al investigated the turbulent plasma jet and reported that the mass flow rate of the ambient air entrained into the turbulent plasma jet is comparatively large and almost directly proportional to the mass flow rate at the jet inlet.…”
Section: Introductionmentioning
confidence: 83%